International monetary transmission and exchange rate regimes: Floaters vs. non-floaters - Soyoung Kim; Doo Yong Yang (Asian Development Bank Institute (ADBI), 2009)
This paper analyzed the impact of United States (US) monetary shocks on the economies of selected East Asian countries using a structural vector autoregression model. We found that the impacts of the US monetary shocks on domestic interest rates and exchange rates contradict conventional wisdom. The conventional exchange rate channel is unlikely to play much role in the transmission of US monetary policy shocks to floating exchange rate regimes in East Asian countries, excluding Japan. In these countries, the domestic interest rate responds strongly to US interest rate changes, largely by authorities giving up monetary autonomy due to fear of floating. On the other hand, the domestic interest rate does not respond much to changes in US rates in the countries with a fixed exchange rate regime and capital account restrictions, such as the People's Republic of China and Malaysia. This may suggest that the countries with a fixed exchange rate regime enjoy a higher degree of monetary autonomy, probably with the help of capital account restrictions.
Keywords: F33; F32; 330; Geldpolitik; Schock; USA; Transmissionsmechanismus; Vergleich; Fester Wechselkurs; Flexibler Wechselkurs; Asien